2015
DOI: 10.4049/jimmunol.1402933
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-26b Modulates the NF-κB Pathway in Alveolar Macrophages by Regulating PTEN

Abstract: NF-κB is one of the best-characterized transcription factors, providing the link between early membrane-proximal signaling events and changes in many inflammatory genes. MicroRNAs are small non-coding RNAs that regulate gene expression at the post-transcriptional level. Here, we evaluated the role of miR-26b in lipopolysaccharide (LPS)-induced inflammatory response in bovine alveolar macrophages (bAMs). LPS stimulation of bAMs upregulated miR-26b at 1 h, and down-regulated miR-26b at 6 and 36 h. Overexpression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 66 publications
0
37
0
Order By: Relevance
“…Several miRNAs are involved in regulating the NF-kB pathway. For example, miR-26b enhances the LPS-induced NF-kB signaling pathway and the production of proinflammatory factors by targeting PTEN (54). Furthermore, miR-3570 inhibits the bacteria-induced inflammatory response of miiuy croaker via the MyD88-mediated NF-kB signaling pathway by targeting MyD88 (55).…”
Section: Discussionmentioning
confidence: 99%
“…Several miRNAs are involved in regulating the NF-kB pathway. For example, miR-26b enhances the LPS-induced NF-kB signaling pathway and the production of proinflammatory factors by targeting PTEN (54). Furthermore, miR-3570 inhibits the bacteria-induced inflammatory response of miiuy croaker via the MyD88-mediated NF-kB signaling pathway by targeting MyD88 (55).…”
Section: Discussionmentioning
confidence: 99%
“…We found that the potential miRNAs targets of hsa_circRNA_001937 include miR-22-5p, miR-26b-3p, miR-10b-3p, miR-376a-5p and miR-597-3p. MiR-26b participates in the inflammatory response by modulating the NF-κB pathway through targeting PTEN [25]. However, due to the limited known function of circRNAs and miRNAs, a lot of circRNAs/miRNAs interactions should be analyzed in the future.…”
Section: Discussionmentioning
confidence: 99%
“…PTEN, however, interacts with PPM1A in scleroderma 65 and PTEN silencing in macrophages increased LPS-induced expression of TNF-a, IL-1b, IL-6, IL-8, and IL-10. 66 There are apparently contrary findings, however. LPS activation of TLR4 also stimulates miR-718 expression (in macrophages), which impacts PI3K/Akt signaling by targeting PTEN, promoting Akt phosphorylation leading to a decrease in the production of proinflammatory cytokines.…”
Section: Role Of Pten In Tlr4 Signalingmentioning
confidence: 55%